Perancangan Safety Management System Manual Level Institusi Politeknik Penerbangan Indonesia Curug - Lestary, Dwi; Rahayu Surtiningtyas, Sri; Rizkina Aswia, Pangsa (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The Law of the Republic of Indonesia Number 1 of 2009, Part 4, Article 314 Paragraph 1, Concerning Safety Management System for Aviation Service Providers, provides that every aviation service provider is required to create, implement, evaluate, and continuously improve a safety management system guided by the national aviation safety program (Aviation Act, 2009). According to the Regulation of the Minister of Transportation of the Republic of Indonesia, Number 62 of 2017, concerning the Safety Management System, it outlines the scope and application for aviation service providers (CASR 19 Safety Management System, 2017). Therefore, every aviation service provider or approved training organization needs to create a manual or procedure as a guide for implementing and promoting an effective safety management system. In this study, researchers used a type of research method called R&D (research and development). Data collection techniques include preliminary studies through surveys, in-depth interviews, and discussions, as well as product validation. In this journal, the researchers emphasize the literature review related to the manual SMS model.